2019
DOI: 10.1111/evo.13719
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms drive the maintenance of polymorphism at loci subject to strong versus weak fluctuating selection

Abstract: The long‐running debate about the role of selection in maintaining genetic variation has been given new impetus by the discovery of hundreds of seasonally oscillating polymorphisms in wild Drosophila, possibly stabilized by an alternating summer‐winter selection regime. Historically, there has been skepticism about the potential of temporal variation to balance polymorphism, because selection must be strong to have a meaningful stabilizing effect—unless dominance also varies over time (“reversal of dominance”)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 44 publications
1
64
0
Order By: Relevance
“…Our observation that seasonal adaptation is polygenic and rapid suggests that there exists a substantial number of common polymorphisms that are subject to strong fluctuating selection that are nonetheless maintained across the range of D. melanogaster . The most straightforward explanation of these results is that these polymorphisms are subject to some form of balancing selection (Bertram and Masel, 2019; Charlesworth, 2015; Gulisija and Kim, 2015, Levene, 1953; Wittmann et al, 2017). Pervasive balancing selection is consistent with the recent realization that simple models of mutation-selection balance are inconsistent with the extent of quantitative genetic variation in a variety of fitness related traits (Charlesworth, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observation that seasonal adaptation is polygenic and rapid suggests that there exists a substantial number of common polymorphisms that are subject to strong fluctuating selection that are nonetheless maintained across the range of D. melanogaster . The most straightforward explanation of these results is that these polymorphisms are subject to some form of balancing selection (Bertram and Masel, 2019; Charlesworth, 2015; Gulisija and Kim, 2015, Levene, 1953; Wittmann et al, 2017). Pervasive balancing selection is consistent with the recent realization that simple models of mutation-selection balance are inconsistent with the extent of quantitative genetic variation in a variety of fitness related traits (Charlesworth, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a population genetic model by Wittmann and colleagues (Wittmann et al, 2017) has demonstrated that seasonally varying selection can indeed maintain fitness related genetic variation at many loci throughout the genome provided that dominance shifts from season to season in such a way that, on average, the seasonally favored allele remains slightly dominant (Curtsinger et al, 1994). These recent models, along with others that highlight the importance of population cycles (Bertram and Masel, 2019), as well as overlapping generations and age structure (Bertram and Masel, 2019; Ellner, 1996; Ellner and Hairston, 1994; Ellner and Sasaki, 1996), suggest that seasonal adaptation and adaptive tracking (Kain et al, 2015) could be an important feature of organisms such as Drosophila that have multiple generations per year (Behrman et al, 2015). More generally, it is possible that adaptive tracking of environmental fluctuations on rapid time scales might be more common than generally acknowledged and has been hidden from us due to the difficulty of detecting such adaptive tracking reliably (Lynch and Ho, 2020) and from the lack of finely resolved temporal data (Buffalo and Coop, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Fluctuating selection can maintain trait variation (McDonald and Ayala 1974; Calsbeek et al. 2010; Bertram and Masel 2019), and may explain why we observe intraspecific variation in metabolic rates (Sasaki and Ellner 1997). A continually shifting environment where different phenotypes are favored under different conditions should maintain phenotypic variation.…”
mentioning
confidence: 81%
“…For instance, a population genetic model by Wittmann and colleagues (Wittmann et al, 2017) has demonstrated that seasonally varying selection can indeed maintain fitness related genetic variation at many loci throughout the genome provided that dominance shifts from season to season in such a way that, on average, the seasonally favored allele remains slightly dominant (Curtsinger et al, 1994). This model, along with others that highlight the importance of population cycles (Bertram and Masel, 2019), as well as overlapping generations and age structure (Bertram and Masel, 2019;Ellner, 1996;Ellner and Hairston, 1994;Ellner and Sasaki, 1996), suggest that seasonal adaptation and adaptive tracking (Kain et al, 2015) could be an important feature of organisms such as Drosophila that have multiple generations per year (Behrman et al, 2015, but see Botero et al, 2015). More generally, it is possible that adaptive tracking of environmental fluctuations on rapid time scales might be more common than generally acknowledged and has been hidden from us due to the difficulty of detecting such adaptive tracking reliably (Lynch and Ho, 2020) and from the lack of finely resolved temporal data (Buffalo and Coop, 2020).…”
Section: Introductionmentioning
confidence: 99%